2011
DOI: 10.1161/hypertensionaha.111.170506
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Deteriorates Endothelial Progenitor Cells

Abstract: A pproximately 15 years ago it was discovered that the bone marrow and blood harbor stem cells with angiogenic potential. 1 Because some of these stem cells express endothelial markers, it is believed that they are endothelial progenitor cells (EPCs) that will contribute to the maintenance of the circulatory system and develop into adult endothelial cells. Many studies followed to unravel the physiological role and the therapeutic application of EPCs. All of these research endeavors did not yet lead to a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In EPCs, this proangiogenic effect depends on NADPH oxidase activation and enhanced VEGF anti-apoptotic function through upregulation of VEGFR2 and improved NO release, as well as on PI3K (phosphoinositide 3-kinase)/Akt signalling [72][73][74]. The deleterious effects of AngII arise from chronic stimulation and consist of two consecutive phases [75]. In the first phase, taking place between days 2 and 5 of stimulation of EPCs with AngII, an AT 1 -receptormediated increase in NADPH oxidase activity leads to ASK-1 (apoptosis signal-regulating kinase-1)/JNK (CJun N-terminal kinase)/p38 MAPK (mitogen-activated protein kinase)/Bax/Bcl2-signalling-induced apoptosis involving caspase 3 [76].…”
Section: Role Of Angii At 1 Receptors and At 2 Receptors In Epcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EPCs, this proangiogenic effect depends on NADPH oxidase activation and enhanced VEGF anti-apoptotic function through upregulation of VEGFR2 and improved NO release, as well as on PI3K (phosphoinositide 3-kinase)/Akt signalling [72][73][74]. The deleterious effects of AngII arise from chronic stimulation and consist of two consecutive phases [75]. In the first phase, taking place between days 2 and 5 of stimulation of EPCs with AngII, an AT 1 -receptormediated increase in NADPH oxidase activity leads to ASK-1 (apoptosis signal-regulating kinase-1)/JNK (CJun N-terminal kinase)/p38 MAPK (mitogen-activated protein kinase)/Bax/Bcl2-signalling-induced apoptosis involving caspase 3 [76].…”
Section: Role Of Angii At 1 Receptors and At 2 Receptors In Epcsmentioning
confidence: 99%
“…Employing AT 1 -receptor-KO MNCs and BM transplants in WT and ApoE (apolipoprotein E)-KO mice, it was shown that AT 1 receptor signalling affects vascular repair function and thus promotes atherogenesis [76]. As commented in detail above, it is still unknown whether these in vivo vascular effects solely depend on EPCs or involve an interplay with inflammatory cells or even BM stromal cells [75].…”
Section: Role Of Angii At 1 Receptors and At 2 Receptors In Epcsmentioning
confidence: 99%
“…It is known that the effects of Ang II on EPCs are mediated by its interactions with AT1 and AT2 receptors [ 22 ]. Wassmann et al reported that the Ang II-induced detrimental effects originate from AT1R receptor signaling in EPCs [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…128 However, chronic stimulation of this receptor eventually results in a decrease of both EPC levels and functioning. 129,130 Regardless, evidence points to a local RAS being integral to the proliferation, differentiation, and proper function of many cells within the bone marrow, especially when faced with hematopoietic stress.…”
Section: Ras In Bone Marrowmentioning
confidence: 99%